Portal vein thrombosis is associated with an increased risk of bone fractures. - Simon Johannes Gairing; Peter Robert Galle; Jörn Markus Schattenberg; Karel Kostev; Christian Labenz (PLoS ONE, 2022)
Background Portal vein thrombosis (PVT) is a rare but severe disease that often leads to portal hypertension-related complications. It is well-known that patients with portal hypertension associated with liver cirrhosis are at increased risk for bone fractures, however data on the impact of PVT on fracture risk are lacking. Aims This study aimed to explore the impact of PVT on the incidence of bone fractures in a large German primary care cohort. Methods Patients with PVT were extensively matched to non-PVT individuals in a 1:5 ratio. The primary outcome of the study was the incidence of any bone fracture. Results This study included 596 patients with PVT and 2,980 non-PVT individuals. During five years of follow-up, the cumulative incidence of bone fractures was significantly higher in PVT patients (n = 87, 13.6%) than in those without PVT (n = 186, 6.7%) (p<0.001). In Cox-regression analyses, PVT was positively associated with bone fractures (HR: 2.16; 95% CI: 1.59-2.93). This association was stronger in women (HR: 2.55; 95% CI: 1.65-3.95) than in men (HR: 1.87; 95% CI: 1.22-2.87). The strongest association was observed in the age group 51-60 years (HR: 2.50, 95% CI: 1.40-4.47). The association between PVT and bone fractures was maintained in subgroup analyses of patients with (HR: 2.03, 95% CI: 1.13-3.63) and without liver cirrhosis (HR: 1.82, 95% CI: 1.28-2.58). Conclusions PVT is independently associated with a higher incidence of bone fractures. Patients with PVT should be critically evaluated for fracture risk and preventive measures should be considered.